Immunopathologic characterization of healthy subjects in an endemic area for pemphigus foliaceus: Comparative study with relatives - Ramos, Willy (2024)
Introduction: endemic pemphigus foliaceus (PFE) has been described at the beginning of the 50s in the peruvian forest. In 2006,Ortega & col. reported the presence of desmoglein 1 antibodies in Pueblo Libre, Ucayali. Nevertheless, immune reports does not exist on patients relatives with PFE in the zone.Objetives: to compare the immunopathologic profiles of healthy subjects from Pueblo Libre (an area in Ucayali, endemic for pemphigus foliaceus), with healthy relatives of patients with endemic pemphigus foliaceus (EPF) and healthy controls from non-endemic areas.Materials and methods: this is a prospective multicentric study performed from June to August 2006. The sample consisted of 41 healthy subjects from the Pueblo Libre community, 11 relatives of EPF patients and 20 healthy subjects from non-endemic areas. Blood samples were obtained for immunopathologic studies (ELISA technique for antibodies against desmoglein-1 and desmoglein- 3). The immunopathologic profiles of each group were compared. Standardization of ELISA was performed using the analysis of receptor operative characteristics (ROC) to find appropriate cut-off values.Results: in Pueblo Libre, the prevalence of antibodies against desmoglein-1 was 46,3%. The predominant pattern was 56,3% for IgG1 and 62,5% for IgG2. Antibodies against desmoglein-3 were found in 31,7% of the sample. A high correlation was found between the index values of antibodies against desmoglein-1 and desmoglein-3. (r=0.76); this is statistically significant, with an alpha = 0,001. The frequency of antibodies against desmoglein-1 was 45,5% in the relatives of EPF patients; the predominant pattern was 63,6% for IgG1 and 54,5% for IgG2. Antibodies against desmoglein-1 were detected in two healthy subjects from non-endemic areas; antibodies against desmoglein-3 were not detected.Conclusion: healthy subjects who are exposed to environmental factors in a focus of endemic pemphigus foliaceus and the relatives of patients with EPF develop non-pathogenic antibodies against desmoglein-1 and -3 with similar immunologic profiles.